2013
DOI: 10.1039/c3cp51745d
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxations and conduction mechanisms in polyether–clay composite polymer electrolytes under high carbon dioxide pressure

Abstract: The composite material P(EO/EM)-Sa consisting of synthetic saponite (Sa) dispersed in poly[ethylene oxide-co-2-(2-methoxyethoxy)ethyl glycidyl ether] (P(EO/EM)) is studied by "in situ" measurements using broadband electrical spectroscopy (BES) under pressurized CO2 to characterize the dynamic behavior of conductivity and the dielectric relaxations of the ion host polymer matrix. It is revealed that there are three dielectric relaxation processes associated with: (I) the dipolar motions in the short oxyethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In the last few years, organic-inorganic hybrid materials have drawn great attention as new generation of high performance materials by reason of their interesting physical and chemical properties obtained from the combination of organic and inorganic materials in single compound [1][2][3][4]. Several studies have reported the use of organic-inorganic hybrid materials in optoelectronic or optical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, organic-inorganic hybrid materials have drawn great attention as new generation of high performance materials by reason of their interesting physical and chemical properties obtained from the combination of organic and inorganic materials in single compound [1][2][3][4]. Several studies have reported the use of organic-inorganic hybrid materials in optoelectronic or optical applications.…”
Section: Introductionmentioning
confidence: 99%
“…9 The gas was pre-dried over a type-A zeolite bed in order to exclude any traces of water from the CO 2 , which could give rise to proton conductivity in the materials. This measurement setup allowed the measurements to be performed on extremely moisture sensitive materials such as PEO-based polymer electrolytes in totally anhydrous conditions 7 . A manual screw pump allowed the cell pressure to be increased to pressures higher than the gas cylinder.…”
Section: Instruments and Methodsmentioning
confidence: 99%
“…The second goal of the study is addressed by modulating the electric response of the IL, measured with broadband electrical spectroscopy (BES), through the partial pressure of CO 2 (P CO2 ). CO 2 , with a permittivity of ε r = 1.08, 7 acts as a seed of aggregation that enhances the lipophilic behaviour of alkyl chains in the cationic aggregates and easily modulate the nano-morphology of the IL and therefore its electric response and conductivity mechanism.…”
Section: -3mentioning
confidence: 99%
“…Thus, morphology dependent dynamic processes taking place in polymers, which are on multiple length scales and different time scales can be identi-ed in an effort to understand the structural states of these materials. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] To date, various polymeric materials have been, and continues to be, analyzed by DRS. [13][14][15][16][17][18][19][20] In polyurethanes, this technique is mainly used to investigate the local dynamics, dynamic glass transition and indirectly, crystallinity and microphase morphology.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] To date, various polymeric materials have been, and continues to be, analyzed by DRS. [13][14][15][16][17][18][19][20] In polyurethanes, this technique is mainly used to investigate the local dynamics, dynamic glass transition and indirectly, crystallinity and microphase morphology. [21][22][23][24][25][26][27][28] Combination of DSC and DRS enables us to gain a complete understanding of the structural variables, such as so segment type and molecular weight and hard segment structure and content on the molecular mobility and segmental dynamics in polyurethanes.…”
Section: Introductionmentioning
confidence: 99%